Protein O- and C-Glycosylation pathways in Toxoplasma gondii and Plasmodium falciparum. Issue 14 (18th February 2019) - Bandini, Giulia; Albuquerque-Wendt, Andreia; Hegermann, Jan; Samuelson, John; Routier, Françoise H.
Abstract: Apicomplexan parasites are amongst the most prevalent and morbidity-causing pathogens worldwide. They are responsible for severe diseases in humans and livestock and are thus of great public health and economic importance. Until the sequencing of apicomplexan genomes at the beginning of this century, the occurrence of N - and O -glycoproteins in these parasites was much debated. The synthesis of rudimentary and divergent N -glycans due to lineage-specific gene loss is now well established and has been recently reviewed. Here, we will focus on recent studies that clarified classical O -glycosylation pathways and described new nucleocytosolic glycosylations in Toxoplasma gondii, the causative agents of toxoplasmosis. We will also review the glycosylation of proteins containing thrombospondin type 1 repeats by O -fucosylation and C -mannosylation, newly discovered in Toxoplasma and the malaria parasite Plasmodium falciparum. The functional significance of these post-translational modifications has only started to emerge, but the evidence points towards roles for these protein glycosylation pathways in tissue cyst wall rigidity and persistence in the host, oxygen sensing, and stability of proteins involved in host invasion.